Personal insolvency and macroeconomic factor: an empirical investigation in Malaysia - Zuraina, Alias (2020)
Rising household insolvency can unfavourably influence economic monetary development as it prevents people from participating productively or contributing to the economy of a country. Statistics from the Malaysian Department of Insolvency (MDI), 2018 and reports from Malaysia’s Credit Counselling and Debt Management Agency (AKPK), 2019 highlight the number of bankrupt individuals and borrowers under the Debt Management Program (DMP) registered with AKPK are increasing from year to year. Hence, the aim of this research is to investigate the determinants of personal insolvency in Malaysia which focusses on several macroeconomic factors and impaired financing for Islamic and conventional banks that affect personal insolvency in Malaysia. The macroeconomic determinants selected are represented by Industrial Production Index (IPI), House Price Index (HPI), Unemployment (UEMP), and Interest (INT). Meanwhile, secured financing for both Islamic and conventional banking is represented by housing and vehicle. Unsecured financing is measured by personal loan and credit card financing. Finally, this study also seeks to capture impaired financing (previously known as non-performing loan (NPL) as a measurement for quality of loans. By assessing the long run and short run cointegration relationship between personal insolvency and the selected macroeconomic variables, this study employs the Auto-Regressive Distributed Lag (ARDL) Model. By employing Bounds testing approach and Vector Autoregression (VAR) model for quarterly data covering the period from 2007Q1 to 2016Q4, this study documents evidence that there are long and short run dynamics from endogenous independent variables such as macroeconomics, secured and unsecured financing as well as impaired financing to personal insolvency in Malaysia. The result of this study further suggest that HPI has a positive significant impact on Personal Insolvency during the period of analysis. As there is a positive significant relationship between HPI and personal insolvency in the long run horizon, it implies that the government can consider policy ramifications to curb excessive increase in house price and should take an initiative to control the property price in order to mitigate any bubble in asset price that may benefit to the borrowers. Changes in house price have a direct effect on household wealth, present and future income which affects the consumption decision over the life cycle as well as stability of the financial system in Malaysia. Therefore banking industry should being aware of the determinants of personal insolvency in Malaysia and thus help the Banks to develop and introduce the innovative products. In this regard, the existence of AKPK should continue to strategies better awareness programmes to equip the public financial literacy and contributes to a sound and robust financial system by creating a financial savvy in order to help individual borrowers managing their finances